2002
DOI: 10.1037/0096-1523.28.2.367
|View full text |Cite
|
Sign up to set email alerts
|

Change detection in multi-voice music: The role of musical structure, musical training, and task demands.

Abstract: This study evaluated the relationship between primitive and scheme-driven grouping (A. S. Bregman, 1990) by comparing the ability of different listeners to detect single note changes in 3-voice musical compositions. Primitive grouping was manipulated by the use of 2 distinctly different compositional styles (homophony and polyphony). The effects of scheme-driven processes were tested by comparing performance of 2 groups of listeners (musicians and nonmusicians) and by varying task demands (integrative and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
4
11
0
1
Order By: Relevance
“…In music, the melody is typically carried by the upper voice and the ability to parse out the melody from other voices is a fundamental musical skill. Consistent with previous behavioral and cortical studies, [24][25][26][27] we found that musicians demonstrated larger subcortical responses to the harmonics of the upper note relative to the lower note. In addition, an acoustic correlate of consonance perception (i.e., temporal envelope) was more precisely represented in the musician group.…”
Section: Subcortical Representation Of Timbresupporting
confidence: 91%
“…In music, the melody is typically carried by the upper voice and the ability to parse out the melody from other voices is a fundamental musical skill. Consistent with previous behavioral and cortical studies, [24][25][26][27] we found that musicians demonstrated larger subcortical responses to the harmonics of the upper note relative to the lower note. In addition, an acoustic correlate of consonance perception (i.e., temporal envelope) was more precisely represented in the musician group.…”
Section: Subcortical Representation Of Timbresupporting
confidence: 91%
“…In general, higher pitched instruments (e.g., violin) or voices (e.g., soprano) often play the role of a leading theme in music as written by composers and performed by players. The effect of voice on the MMNm is also in agreement with observations in behavioral studies that higher-pitched melodies are easily recognized in infants (Trehub & Trainor, 1998;Zenatti, 1969) and in both musically trained and untrained subjects (Crawley et al, 2002;Palmer & Holleran, 1994). Because the MMN is thought to increase and become early according to the salience of mental representation, our results indicate that the higher voice is already dominant in sensory memory.…”
Section: High Voice Advantage On Mmnmsupporting
confidence: 80%
“…It is also easier to detect wrong notes if the melodies are more harmonically related (Sloboda & Edworthy, 1981). Several other studies have demonstrated that this detection is more robust for the higher than the lower melodic line, even in school-age children (Zenatti, 1969), whereas recognition of lower-pitched melodies can be better achieved by more experienced listeners (e.g., musicians) than naïve subjects (Crawley, Acker-Mills, Pastore, & Weil, 2002;Palmer & Holleran, 1994). Moreover, these studies have shown that listening task differences between attending to one melodic line versus attending to integrated harmony does not change the exceptional dominance of recognition for the higher over lower melody lines, although musicians perform better than nonmusicians in detecting changes in the low stream.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous behavioral and electrophysiological research has demonstrated results consistent with our study. For example, behavioral studies have shown that changes occurring in the upper voice are more easily detected than those in the middle or lower voice (Palmer and Holleran, 1994;Crawley et al, 2002). Furthermore, electrophysiological studies showed larger and earlier mismatch negativity magnetic field (MMNm) responses for deviations in the upper voice melody than in the lower voice (Fujioka et al, 2005(Fujioka et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%